Impact of Smoking Status and Nicotine Dependence on Academic Performance of Health Sciences Students - Alqahtani JS; Aldhahir AM; Alanazi Z; Alsulami EZ; Alsulaimani MA; Alqarni AA; Alqahtani AS; AlAyadi AY; Alnasser M; AlDraiwiesh IA; Alghamdi SM; Almarkhan HM; et al. (Dove Medical Press, 2023)
Jaber S Alqahtani,1 Abdulelah M Aldhahir,2 Zaid Alanazi,3 Emad Zahi Alsulami,4 Mujahid A Alsulaimani,5 Abdullah A Alqarni,6 Abdullah S Alqahtani,1 Ayadh Yahya AlAyadi,1 Musallam Alnasser,1 Ibrahim A AlDraiwiesh,1 Saeed M Alghamdi,7 Hussam M Almarkhan,1 Abdullah S Alsulayyim,2,8 Saad M AlRabeeah,1 Mohammed D AlAhmari1 1Department of Respiratory Care, Prince Sultan Military College of Health Sciences, Dammam, 34313, Saudi Arabia; 2Respiratory Therapy Department, Faculty of Applied Medical Sciences, Jazan University, Jazan, 45142, Saudi Arabia; 3Family Medicine Department, Northern Area Armed Forces Hospital (NAAFH), Hafar Al Batin, Saudi Arabia; 4Family Medicine Department, Armed Forces Hospital in King Abdulaziz Airbase, Dhahran, Saudi Arabia; 5Basic Medical Unit, Prince Sultan Military College of Health Sciences, Dammam, 34313, Saudi Arabia; 6Department of Respiratory Therapy, Faculty of Medical Rehabilitation Sciences, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 7Respiratory Care Program, College of Applied Medical Sciences, Umm Al-Qura University, Makkah, 24382, Saudi Arabia; 8National Heart and Lung Institute, Imperial College London, London, SW7 2BX, UKCorrespondence: Jaber S Alqahtani, Department of Respiratory Care, Prince Sultan Military College of Health Sciences, Dammam, 34313, Saudi Arabia, Email Alqahtani-Jaber@hotmail.comBackground: Smoking behavior has been associated with poor academic performance among adult students worldwide. However, the detrimental effect of nicotine dependence on several students' academic achievement indicators is still unclear. This study aims to assess the impact of smoking status and nicotine dependence on grade point average (GPA), absenteeism rate and academic warnings among undergraduate health sciences students in Saudi Arabia.Methods: A validated cross-sectional survey was conducted, in which, participants responded to questions evaluated cigarette consumption, urge to consume and dependency, learning performance, days of absentees, and academic warnings.Results: A total of 501 students from different health specialties have completed the survey. Of whom, 66% were male, 95% ranging between the age of 18- 30 years old, and 81% reported no health issues or chronic diseases. Current smokers estimated to be 30% of the respondents, of which 36% revealed smoking history of 2- 3 years. The prevalence of nicotine dependency (high to extremely high) was 50%. Overall, smokers had significantly lower GPA, higher absenteeism rate, and higher number of academic warnings when compared to nonsmokers (p< 0.001). Heavy smokers demonstrated significantly less GPA (p=0.036), higher days of absences (p=0.017), and more academic warnings (p=0.021) compared to light smokers. The linear regression model indicated a significant association between smoking history (increased pack-per-year) and poor GPA (p=0.01) and increased number of academic warning last semester (p=0.01), while increased cigarette consumption was substantially linked with higher academic warnings (p=0.002), lower GPA (p=0.01), and higher absenteeism rate for last semester (p=0.01).Conclusion: Smoking status and nicotine dependence were predictive of worsening academic performance, including lower GPA, higher absenteeism rate and academic warnings. In addition, there is a substantial and unfavorable dose-response association between smoking history and cigarette consumption with impaired academic performance indicators.Keywords: smoking, nicotine dependence, academic performance, health sciences, student